Analysis of soil electrical resistivity and hydraulic conductivity relationship for characterisation of lithology inducing slope instability in residual soil - Oladunjoye P. Olabode; Lim H. San (International Journal of Geo-Engineering, 2023)
Key points Relationship between soil electrical resistivity and hydraulic conductivity were examined for assessment of lithology inducing shallow-landslide. Soil electrical resistivity delineated a boundary between two contrasting resistive and conductive lithologies at 4 m depth. Strong correlation ranged between R2 = 0.9153 to 0.9702 were observed between soil resistivity and hydraulic conductivity for the soil samples examined. The conductive lithology with low hydraulic conductivity below 4 m depth was responsible for the occurrences of the shallow-landslides.